Evaluasi Desain Antarmuka Pengguna Website Kabupaten Blitar Menggunakan Metode Usability Testing (Studi Pada Dinas Pemerintahan Kabupaten Blitar) - Mukhammad Yusuf; Aditya Rachmadi; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Information is the result of processing data in any form that is more meaningful to the recipient. Information describes a real event and is used for decision making. Website http://blitarkab.go.id which is the Blitar District Government website is the source of information for the people of Blitar Regency. But if the information is difficult and rare to update how the information can easily reach the community. By doing usability testing, the system can be evaluated so that the system can be easily used by the user. This research begins with the process of determining the sample and population to perform usability with the task already created. The next step is the process of measuring website usability using the Keystroke Level Model methodology by assigning tasks to test targets. The purpose of usability measurement is to measure the usability level of learnability, efficiency, memorability, errors, and satisfaction of the Blitar district website. The results are time, error, and reaction of test target during testing. Analysis of usability level that has been done will be a reference of the recommendation improvement website of Blitar. The improvement recommendations are based on the HHS guidelines and the website development guidelines of the local government website of USDRP (Urban Sector Development Reform Project) participants to meet the minimum standards of government websites